Merton G. Henry: A Legacy of Leadership - Richards, David (Maine Policy Review, 2018)
David Richards describes the many qualities of leadership manifested by Merton G. Henry: dedication, moderation, friendship, wisdom, compassion, humor, knowledge, grace, and humility.